Sagittal anatomy in laparoscopic radical right hemicolectomy for right colon cancer based on membrane anatomy theory - Pan, Guofeng; Zhang, Weihong; Huang, Shiyu; Wu, Jihuang; Chen, Jian; Weng, Jianbin; Zhu, Zipeng; Guo, Zhixing; Xu, Yanchang (Frontiers in Oncology, 2025)
ObjectivesThis study aimed to explore the concept of sagittal anatomy in laparoscopic radical right hemicolectomy through the lens of membrane anatomy.MethodsA retrospective study reviewed clinical records of 128 patients with right colon cancer who received laparoscopic radical right hemicolectomy at the Department of Gastrointestinal Surgery Unit 1, The First Hospital of Putian City, Fujian Province, between December 2020 and December 2022. Among the participants, 70 were male and 58 were female, with an average age of 62 years. All patients received standardized laparoscopic radical right hemicolectomy, following the principles of sagittal anatomy. The surgical technique comprised three steps: cephalic, caudal dorsal, and CVL+D3. Anatomical landmarks were exposed to ensure quality control for each surgical area. Intraoperative photographs were captured, and data on operation time, lymph node harvest, intraoperative blood loss, and postoperative outcomes were collected.ResultsAll laparoscopic procedures were successfully completed without the need for conversion to open surgery or the occurrence of intraoperative complications. Lymph node dissection was successfully performed in all patients, and specimens were examined pathologically. The average number of lymph nodes harvested, operation time, and intraoperative blood loss were 20.25 ± 3.23, 153.36 ± 11.49 minutes, and 42.15 ± 5.82 mL, respectively. All patients were diagnosed with adenocarcinoma based on pathological examination. The 3-year overall survival rate was 78.2%.ConclusionWhen viewed through the lenses of embryological development and membrane anatomy, the sagittal approach to laparoscopic radical right hemicolectomy proves to be both safe and feasible, contributing to a more standardized and regulated approach to the procedure.